69.4k views
4 votes
If h(x) = x – 7 and g(x) = x2, which expression is equivalent to (gxh)(5)

User Zote
by
5.9k points

2 Answers

4 votes
We want g(h(5)).

First find h(5).

h(5) = 5 - 7

h(5) = -2

We now find g(-2).

g(x) = x^2

g(- 2) = (-2)^2

g(-2) = 4

In conclusion, g(h(5)) = 4.
User Amiraslan
by
5.6k points
3 votes

Answer:


(g* h)(5)=-50

Explanation:

Given : If
h(x)=x-7 and
g(x)=x^2

To find : Which expression is equivalent to
(g* h)(5)

Solution :

If
h(x)=x-7 and
g(x)=x^2


(g* h)(x)=g(x)* h(x)

Substitute the values,


(g* h)(x)=x^2* (x-7)


(g* h)(x)=x^3-7x^2

Substitute x=5,


(g* h)(5)=5^3-7(5)^2


(g* h)(5)=125-7(25)


(g* h)(5)=125-175


(g* h)(5)=-50

Therefore,
(g* h)(5)=-50

User Slaurent
by
5.7k points